Medical confidentiality in the digital era: an analysis of physician-patient relations - Kato Lettieri, Gabriela (2021)
The study analyzes confidentiality in the physician-patient relations, addressing how new technologies, such as social media, influence professional practice, and assessing the professionals’ knowledge regarding situations in which confidentiality can be broken without legal consequences. This crosssectional, quantitative and exploratory research took place between October and November 2019, involving 116 physicians who answered a structured questionnaire with 19 questions, among which five assessed knowledge on professional secrecy according to the Code of Medical Ethics and the Brazilian legal system. Physicians who answered three or more questions correctly were considered to have satisfactory knowledge on social media use and medical confidentiality (only 55.2% of respondents). Results reveal the importance of continuing medical education, especially regarding medical confidentiality.